Rediscovery of Furipterus horrens (Chiroptera: Furipteridae) in Costa Rica - Pineda Lizano, Willy (2018)
Furipterus horrens is a small insectivorous bat with distinct clawless tiny thumbs, and with a patchy geographic distribution in the Neotropics. We report the rediscovery of F. horrens in Costa Rica 44 years after it was first recorded. A colony of 100–130 individuals, each one with the distinctive external and morphological characteristics of the species, was found roosting in the lower parts of the floor of bungalows located in the Sarapiquí area. The rediscovery of this species validates the protection of several rainforest fragments through ecotourism, a modern way to balance human development and biodiversity conservation